2021
DOI: 10.1007/s00592-021-01720-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucose variability and periodontal disease in type 1 diabetes: a cross-sectional study—The “PAROdontopatia e DIAbete” (PARODIA) project

Abstract: Aims Periodontal disease (PD) is a chronic inflammation of periodontal tissue associated with infection from specific anaerobic pathogens contained in dental plaque. Both type 1 and type 2 diabetes are associated with an increased prevalence of PDs. A two-way relationship between diabetes and periodontitis has been proposed, with diabetes increasing the risk for periodontitis, and periodontal inflammation negatively affecting glycaemic control. To date, the relationship between PD and glucose var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Progression of untreated PD leads to tooth loss, impaired quality of life (Cairo et al, 2018) and significant systemic inflammation (Linden et al, 2013). Several studies showed an association between PD and systemic diseases such as type 1 (Dicembrini et al, 2020, 2021) and type 2 diabetes mellitus (Genco & Borgnakke, 2013), cardiovascular disease (Tonetti & Van Dyke, 2013) and also Chronic kidney disease (CKD) (Chambrone et al, 2013; Deschamps‐Lenhardt et al, 2019; Kapellas et al, 2019; Zhao et al, 2018). Interestingly, PD and CKD share common risk factors, such as age, smoking and poorly controlled diabetes (Fisher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Progression of untreated PD leads to tooth loss, impaired quality of life (Cairo et al, 2018) and significant systemic inflammation (Linden et al, 2013). Several studies showed an association between PD and systemic diseases such as type 1 (Dicembrini et al, 2020, 2021) and type 2 diabetes mellitus (Genco & Borgnakke, 2013), cardiovascular disease (Tonetti & Van Dyke, 2013) and also Chronic kidney disease (CKD) (Chambrone et al, 2013; Deschamps‐Lenhardt et al, 2019; Kapellas et al, 2019; Zhao et al, 2018). Interestingly, PD and CKD share common risk factors, such as age, smoking and poorly controlled diabetes (Fisher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggests that the glycaemic control is of key importance in determining increased risk of periodontal disease [30]. This hypothesis was based on ndings of Dicembrini et al [9] and Jensen et al [34] who reported a signi cant correlation between the prevalence of PD and glycaemic control, which increased severity of early biomarkers of periodontal individuals. Pro-in ammatory cytokines are elevated in diabetes, which can increase the connective tissue damage and impair wound healing [11,13,14,35].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is a chronic in ammation of periodontal tissue associated with infection from Gram-negative bacteria contained in dental plaque, promoting a chronic and progressive local in ammatory response [4][5][6][7][8]. The progressive destruction of connective tissue and bone support can result in tooth loss and systemic in ammation [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism is in disrupting the body's ability to mount a response and immune dysregulation. Increased inflammation increases the assault to the alveoli 16 . Diabetes also does not exist in isolation but is comorbid with a lot of other risk factors that are not independently associated such as hypertension and death.…”
Section: Introductionmentioning
confidence: 99%